The Role of the Accountant in Strategic Planning: A Model for the 1990s. - Graham, Roger C. (The Accounting Review, 1994)
Abstract Reviews the book `The Role of the Accountant in Strategic Planning: A Model for the 1990s,' by Crispin Simon.